Survey of modeling methods in cyber-physical system - Ren-fa LI; Fan YANG; Guo-qi XIE; Jing HUANG; Meng-qin DUAN (Tongxin xuebao)
Cyber-physical system(CPS)not only contains the discrete calculation process and network communication,but also involves in the handling of continuous physical events.Based on discrete system and continuous system,some existing modeling theories and development tools were introduced,and their applications in CPS were summarized,and a brief introduction on how to solve the problem was given.Finally,on the basis of the difficulty to be solved in CPS,four practical ways for researchers were put forward to solve the CPS modeling problem.